Enuresis, a problem to be faced in Primary Health Care due to its educational component - Mislandy Caridad González Guevara; Helena Fernández Esperanza; Marta Amelia Hernández Martínez; Owen Daniel González Cruz (Acta Médica del Centro)
Introduction: enuresis is a common disorder throughout the world; however, it is abnormal after five years of age, resulting in social isolation and disruptions in the family unit. Objective: to characterize children who suffer from primary enuresis and who were treated in the Pediatric Mental Health Consultation and referred from their Health Area. Methods: a cross-sectional descriptive study was carried out in the Pediatric Mental Health Clinic of the “Chiqui Gómez Lubián” Polyclinic of the Municipality of Santa Clara in the period from January 2019 to January 2020. The population consisted of 14 children. Results: the male sex prevailed (71.4%) and 64.3% were grouped between the ages of seven and nine, nine had a family pathological history and 64.3% were affected by parental divorce; They reported poor concentration and interaction in the group, average or poor school performance, and sadness. Conclusions: enuresis is a disease that affects children and the family with a high biopsychosocial significance, which is why an integrative approach is necessary in its clinical-therapeutic approach.